2009
DOI: 10.1097/jgp.0b013e3181987730
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Cognition, Apolipoprotein E Genotype: Latent Class Approach to Identifying Subtype

Abstract: Objectives-Possessing the ε4 allele of apolipoprotein E (APOE-ε4) genotype is associated with cognitive impairment in non-demented older adults. We hypothesized that we might find a subtype of depression related to impaired cognitive performance associated with the APOE-ε4 allele. Design-A survey conducted between 2001-2003 with APOE genotyping.Setting-Primary care offices in the Baltimore, Maryland area.Participants-The study sample consisted of 305 adults aged 65 or older with complete information on APOE ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…The evidence supported the idea that the presentation of depression symptoms among older adults is heterogeneous. Results showing that the majority of participants reported low levels of depression symptoms are similar to the findings obtained with similar methods in samples of adults and older adults (Bogner, Richie, de Vries, & Morales, 2009;Chen, Eaton, Gallo, & Nestadt, 2000) indicating that poor mental health is not the norm among older individuals (Alexopoulos et al, 2002). The prevalence of individuals with high levels of depression symptoms in the current sample is consistent with epidemiological data from older adults (Lyness, Caine, King, Cox, & Yoediono, 1999;Steffens et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…The evidence supported the idea that the presentation of depression symptoms among older adults is heterogeneous. Results showing that the majority of participants reported low levels of depression symptoms are similar to the findings obtained with similar methods in samples of adults and older adults (Bogner, Richie, de Vries, & Morales, 2009;Chen, Eaton, Gallo, & Nestadt, 2000) indicating that poor mental health is not the norm among older individuals (Alexopoulos et al, 2002). The prevalence of individuals with high levels of depression symptoms in the current sample is consistent with epidemiological data from older adults (Lyness, Caine, King, Cox, & Yoediono, 1999;Steffens et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Other genes associated with differences in cognition such as apolipoprotein E ( APOE ) (48, 49) and Catechol-o-methyl transferase ( COMT ) (50) might also alter results, though these interactions were not examined in this study. Potential gene-gene interactions need to be considered, as one gene’s effect may be modulated by other genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, APOE ε4 carriers with depression were 7.1 times more likely to progress to AD compared to non-APOE ε4 carriers with depression, who were only 1.6 times more likely to develop AD (Irie et al 2008). Bogner et al (2009) found that there was no relationship between APOE status and depression (most notably, thoughts of death or suicide) with cognitive impairment. A more extensive study showed that plasma Aβ42 levels independently predicted late-onset depression and AD development in subjects who had never been depressed or did not have current cognitive impairment, suggesting a common biological etiology for these two conditions (Blasko et al 2010).…”
Section: Apoe Beta Amyloid and Taumentioning
confidence: 95%